Clinical Progression and Load Management For Proximal Hamstring Tendinopathy In A Long-Distance Runner: A Case Report - Cristina Campos-Villegas; Lucía Ortega-Pérez de Villar; Javier Gámez-Payá; Jorge Alarcón-Jiménez; Nieves de Bernardo (North American Sports Medicine Institute, 2024)
# Background and Purpose The characteristics of Proximal Hamstring Tendinopathy (PHT) include deep, localized pain in the region of the ischial tuberosity. Chronic lesions are often found in long-distance runners. Compression of the tendon and shear force at its insertion at the ischial tuberosity during hip flexion/adduction is a key etiologic factor. The aim of this case report is to analyze the effectiveness of an exercise protocol with progression of tendon loading in PHT in an amateur runner, by assessing pain and functional capacity. # Case Description The subject was a 30-year-old male runner. After participating in a 10km race, he experienced an insidious onset of deep buttock pain in the right ischial tuberosity. His pain was aggravated by running on sloped roads and prolonged sitting on hard surfaces, particularly while driving. The visual analog scale (VAS) for pain, the Puranen-Orave test (PO), the Bent-Knee stretch test (BK stretch), the supine plank test, the Victorian Institute of Sport Assessment-proximal hamstring tendons (VISA-H) questionnaire, and the sciatic nerve mobility (via the Slump test) were assessed. The intervention involved a 12-week progressive loading exercise program divided into four phases. # Outcomes The initial pain was reduced at 6 weeks of intervention and further decreased at 12 weeks (VAS from 7, to 5 and to 1). Function increased at 6 weeks and at 12 weeks (VISA-H from 23, to 53, to 80). Sciatic nerve mobility was normal. # Conclusion The progression of training in a subject with PHT tendon injury based on isometric exercise, concentric/eccentric, energy storage, progressively increasing hip flexion was beneficial, increasing function and decreasing pain. Studies with a larger sample size and a more precise methodological design would be necessary to support this type of intervention in clinical practice. # Level of Evidence 5